Effect of Vitamin E and C Supplementation on Liver Enzymes of Mice Exposed to Sodium Nitrate - Hameed, Marah Salim (Diyala Journal of Medicine, 2019)
Background: The liver is the major organ responsible for metabolism, detoxification, and secretory functions in the body. Vitamin C is an essential co-factor, acting as a reducing agent and may have heaptoprotective property. Vitamin E is an antioxidant factor. Sodium nitrate is a salt and an anti-oxidant that is used as a preservative. Objective: To evaluate the effect of sodium nitrate, vitamin E and vitamin C administration on liver enzymes, alanine transaminase, aspartate transaminase and alkaline phosphatase. Materials and Methods: Sixty healthy adult male mice divided randomly into six groups, group 1, received vitamin E solution 0.5 ml / liter distal water daily for 2 weeks. group2, received vitamin C solution 0.5 gm / liter distal water daily for 2 weeks. Group 3, received sodium nitrate solution 0.5gm/liter distal water daily for 2week. Group 4, received sodium nitrate solution orally in dose170 mg/kg body weight and received vitamin E solution 0.5 ml / liter distal water daily for 2 weeks. Group 5, received sodium nitrate solution orally in dose170 mg/kg body weight and received vitamin C solution 0.5 gm / liter distal water daily for 2 weeks. Group 6 (Control), receive distal water daily for 2 weeks. After the last day of administration, the animals were euthanized and blood samples were drawn from the heart by cardiac puncture into plain tubes, and then subjected to biochemical assays. Results: A significant difference in alanine transaminase level was reported between control group and group of mice received vitamin E (P-value = 0.001), vitamin E+ NaNO3 (P value =0.015). No significant difference in alanine transaminase level was reported between control and other groups. Significant difference in aspartate transaminase level reported between control group and group of mice received vitamin E (P-value = 0.000202573), vitamin C (P value = 0.00143), NaNO3 (p value=0.008076). No significant difference in aspartate transaminase level was reported between control and group of mice received (vitamin E+ NANO3) (vitamin C+NANO3) groups. Significant difference in alkaline phosphatase level reported between control group and group of mice received vitamin E (P-value = 4.5E-13), vitamin C (P value = 4.45E-18), (p value=6.17E-06), vitamin E+ NANO3 (p-value=3.68E-15). No significant difference in aspartate transaminase level was reported between control and group received (Vitamin C+ NANO3), p-value = (0.091718). Conclusion: Vitamin E and C have the ability to ameliorate the effect of sodium nitrate in exposed groups although the effect of vitamin E more obvious due to pharmaceutical formulation, finally antioxidant effects of vitamins leads to modulation the nitrate toxicity and hepatoprotective effect.